Shaykh Waliyullah al-Dihlawi dan Konsep-Konsep Kunci dalam Penafsiran Alquran - Djalal, Abdul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2018)
This article attempts to explore the thought of Shaykh Waliyullah al-Dihlawi on the Qur’an and key concepts of the Qur’anic science. By using historical approach and content analysis method, I argue that al-Dihlawi is a Muslim reformist whose thought on understanding the Qur’an is rarely discussed by Indonesian Muslim scholars. He is expert not only in the field of Islamic law, mysticism, and thought, but also in the field of Qur’anic exegesis. His thought and ideas have been referred to and followed by Muslims of Bahrevi and Deoband and has inspired the ideas of neo-Mu’tazilah in India. Through his rational way of thinking, he offers a new light of understanding the Qur’an through historical perspective with regard to the concept of asbab al-nuzul, al-naskh, and the Israelite tales of previous community. Beside the historical consciousness, al-Dihlawi requires also a necessity for understanding the universal message behind the text. These were among the reformist thoughts of al-Dihlawi which arose in the desert of the Muslim traditional conviction.